THE EFFECT OF THE HEALTH EDUCATION OF BREAST SELF-EXAMINATION ON THE KNOWLEDGE AND ATTITUDE OF THE STUDENTS OF MIDWIFERY ACADEMY IN SALATIGA MUNICIPALITY - Maryanti . (STIKES DUTAGAMA KLATEN, 2012)
Background: Due to the lack of appropriate and adequate information on the breast self-examination, the students cannot make early detection on the breast cancer. It has been acknowledged that breast cancer is one of the cancers that cause the high death rate in women after cervical cancer.Objective: The general objective of the research is to investigate the effect of the health education of breast self-examination on the knowledge and attitude of the students of Midwifery Academy in Salatiga municipality. The specific objectives of the research are: (1) investigate the difference of knowledge between the students who are not taught with health education and those who are taught with health education, both prior to and following the treatment; (2) to investigate the difference of attitude between the students who are not taught with health education and those who are taught with health education, both prior to and following the treatment; and (3) to analyze the effect of health education of breast self-examination on the knowledge and attitude of the students.Method: The research used a quasi experiment with a cross-sectional research design. It was conducted at Midwifery Academy in Salatiga municipality. The data of the research were gathered through tests (pre-and post-tests), and questionnaire of Liker’s scale. The data were analyzed by using a two-way analysis of variance (ANOVA).Result: The results of the research show that (1) there is an effect of the health education of breast self-examination on the knowledge of the students as indicated by the value of p = 0.999 in the pre-test and that of p = 1.000 in the post test following the treatment; and (2) there is an effect of the health education of breast self-examination on the attitude of the students as indicated by the value of p = 0.999 in the pre-test and that of p = 1.000 in the post test following the treatment.Conclution: there is the influence of health education on breast self-examination knowledge and attitudes of midwifery students in the municipal salatiga.